2021
DOI: 10.3390/ijms22158156
|View full text |Cite
|
Sign up to set email alerts
|

Isoconazole and Clemizole Hydrochloride Partially Reverse the Xeroderma Pigmentosum C Phenotype

Abstract: Xeroderma Pigmentosum protein C (XPC) is involved in recognition and repair of bulky DNA damage such as lesions induced by Ultra Violet (UV) radiation. XPC-mutated cells are, therefore, photosensitive and accumulate UVB-induced pyrimidine dimers leading to increased cancer incidence. Here, we performed a high-throughput screen to identify chemicals capable of normalizing the XP-C phenotype (hyper-photosensitivity and accumulation of photoproducts). Fibroblasts from XP-C patients were treated with a library of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Xeroderma pigmentosum group C (XPC) is a DNA damage recognition factor and a promoter of nucleotide excision repair that plays an important role in maintaining DNA stability (3). XPC is a key factor in the development of a number of tumor types including lung cancer (4)(5)(6)(7). Our previous study revealed that a reduction in XPC expression can markedly promote the stem cell properties of lung cancer cells and increase the proliferation and migration of lung cancer cells, and a low XPC expression in patients with lung cancer is associated with poor prognosis (8).…”
Section: Introductionmentioning
confidence: 99%
“…Xeroderma pigmentosum group C (XPC) is a DNA damage recognition factor and a promoter of nucleotide excision repair that plays an important role in maintaining DNA stability (3). XPC is a key factor in the development of a number of tumor types including lung cancer (4)(5)(6)(7). Our previous study revealed that a reduction in XPC expression can markedly promote the stem cell properties of lung cancer cells and increase the proliferation and migration of lung cancer cells, and a low XPC expression in patients with lung cancer is associated with poor prognosis (8).…”
Section: Introductionmentioning
confidence: 99%
“…The eight papers published in this SI described case studies that may provide a useful framework for understanding the general molecular defects underlying a broad and diverse spectrum of human diseases. These included multifactorial or polygenic disorders, such as lung cancer (OMIM*612052) and osteoporosis (OMIM*166710) [ 1 , 2 ], or monogenic disorders, such as Long QT Syndrome 1 (LQT; OMIM*192500), Hyaline fibromatosis syndrome (OMIM*228600), Dystrophic epidermolysis bullosa (RDEB; OMIM*226600), Xeroderma Pigmentosum C Phenotype (XP-C; OMIM*278720), and MTHFR deficiency (OMIM*236250) [ 3 , 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…To highlight possible mechanisms of protein destabilisation due to residue change, Savojardo et al explored the structural impact of all 72 reported disease-causing variants of the MTHFR gene [ 8 ]. In other cases, as that of Kobaisi et al, the studied variant depends on the available patient-derived cells to be used as a model system for a specific disease [ 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations